Magnetic stimulation supports muscle and nerve regeneration after trauma in mice. Issue 4 (April 2016) - StÖlting, Meline N.L.; Arnold, Anne Sophie; Haralampieva, Deana; Handschin, Christoph; Sulser, Tullio; Eberli, Daniel
ABSTRACT: Introduction : Magnetic stimulation (MS) has the ability to induce muscle twitch and has long been proposed as a therapeutic modality for skeletal muscle diseases. However, the molecular mechanisms underlying its means of action have not been defined. Methods : Muscle regeneration after trauma was studied in a standard muscle injury mouse model. The influence of MS on the formation of motor units, posttrauma muscle/nerve regeneration, and vascularization was investigated. Results : We found that MS does not cause systemic or muscle damage but improves muscle regeneration by significantly minimizing the presence of inflammatory infiltrate and formation of scars after trauma. It avoids posttrauma muscle atrophy, induces muscle hypertrophy, and increases the metabolism and turnover of muscle. It triples the expression of muscle markers and significantly improves muscle functional recovery after trauma. Conclusions : Our results indicate that MS supports muscle and nerve regeneration by activating muscle–nerve cross‐talk and inducing the maturation of neuromuscular junctions. Muscle Nerve 53 : 598–607, 2016